2014
DOI: 10.1007/s10529-014-1586-2
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of the infectious hematopoietic necrosis virus glycoprotein by flow cytometry

Abstract: The glycoprotein of infectious hematopoietic necrosis virus was truncated to ten overlapping fragments. All fragments were displayed on the inner membrane of the Escherichia coli periplasm. After disruption of the outer membrane, spheroplasts that had anchored with the glycoprotein fragment were incubated with an anti-glycoprotein polyclonal antibody. Prey pairs were detected and quantitated by flow cytometry with all fragments but one, G2, reacting with the polyclonal antibody. The antigenicity of all ten fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The Ja serotype of IPNV ChRtm213 33 and the J genotype IHNV Sn1203 32 are laboratory stocks. IPNV ChRtm213 was propagated in CHSE-214 cells and IHNV Sn1203 was propagated in EPC cells, as described previously 16, 51 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ja serotype of IPNV ChRtm213 33 and the J genotype IHNV Sn1203 32 are laboratory stocks. IPNV ChRtm213 was propagated in CHSE-214 cells and IHNV Sn1203 was propagated in EPC cells, as described previously 16, 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated the co-infection of rainbow trout with IHNV and IPNV under natural conditions 30, 31 . Therefore, in this study, a bivalent DNA vaccine was constructed with the G gene of Chinese IHNV isolate Sn1203 32 and the VP2–VP3 genes of Chinese IPNV isolate ChRtm213 33 . Here, we report the successful design and construction of this bivalent DNA vaccine, designated pCh-IHN/IPN, which induced protective immune responses against IHNV infection, IPNV infection, and co-infection with IHNV and IPNV in the rainbow trout.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been used for the search of immunogenic proteins for viral and bacterial vaccines. In the case of viral vaccines, reverse genetics have been used for the identification of immunogenic proteins for IPNV [ 74 ], peptide scanning for NNV [ 75 ] and IPNV [ 76 ], phage display for infectious salmon anemia virus (ISAV) [ 77 ] and IHNV [ 78 ] while bioinformatics has been used to identify immunogenic proteins for SGIV [ 79 ]. The search of bacterial immunogenic proteins is mostly centered on identifying antigens that provide protective immunity across variant serotypes of the same bacterial species.…”
Section: Application Of Genomic Studies In Vaccine Developmentmentioning
confidence: 99%
“…Infectious hematopoietic necrosis (IHN) is an acute infectious disease that affects fishes and is caused by the infectious hematopoietic necrosis virus (IHNV), which is highly common in salmonids. IHN can cause 90 to 100% mortality in rainbow trout ( Oncorhynchus mykiss ) depending on differences in host species, virus strains, and environmental conditions [ 8 , 9 ]. Based on the significant economic losses caused by infectious hematopoietic necrosis to the global rainbow trout aquaculture industry each year, the World Organization for Animal Health (OIE) listed it as an animal disease that must be declared during import and export.…”
Section: Introductionmentioning
confidence: 99%